2019
DOI: 10.1088/1555-6611/ab286d
|View full text |Cite
|
Sign up to set email alerts
|

Spectrochemical analysis of dates available in Pakistan using laser induced breakdown spectroscopy (LIBS) and laser ablation time-of-flight mass spectrometer (LA-TOF-MS)

Abstract: Laser induced breakdown spectroscopy (LIBS) complemented with laser ablation time-offlight mass spectroscopy (LA-TOF-MS) has been utilized for the spectrochemical analysis of samples of different dates available in Pakistan. The plasma was generated by a focused Q-Switched Nd:YAG laser (532 nm), while a set of four spectrometers were used to capture the optical spectra. For the quantitative analyses of the laser produce plasma, optically thin and local thermodynamic equilibrium conditions were validated. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Moreover, LIBS technique was used to determine the elements existing in any material including plants. Previously, many studies have been conducted on different medicinal plants reporting the presence of elements using LIBS ( Zafar et al, 2019 , Rai et al, 2013 ). Our studies confirmed the presence of eight elements (Si, Fe, Ba, Mg, Ti, Ca, Mg and Cr) indicating that the selected species can be effectively used in industries as a major source of elements.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LIBS technique was used to determine the elements existing in any material including plants. Previously, many studies have been conducted on different medicinal plants reporting the presence of elements using LIBS ( Zafar et al, 2019 , Rai et al, 2013 ). Our studies confirmed the presence of eight elements (Si, Fe, Ba, Mg, Ti, Ca, Mg and Cr) indicating that the selected species can be effectively used in industries as a major source of elements.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was concluded as there is low concentration of Na and K in Pakistani breads whereas the concentrations of magnesium and zinc were higher. It was further found that LIBS is a fast and convenient technique for food analysis (Ahmad et al, 2020;Jovanovic, 2014;Zafar et al, 2019).…”
Section: Ion-selective Electrode Methodsmentioning
confidence: 99%
“…As a tool for detecting adulterants in honey, LIBS is an attractive option since it is fast, inexpensive, waste-free, and does not require sampling. Despite LIBS’s numerous applications, the technology is little explored in food analysis [ 10 , 103 , 104 ] especially for viscous products, such as honey. Since the chemical profile of sweetener syrups differs from the honey in several aspects, such as mineral content, sugars, protein, enzymes, etc.…”
Section: Quality Assurance Chemical Constituent and Risk Assessment O...mentioning
confidence: 99%
“…The LIBS results were also validated through standard techniques, such as ICP-MS on identical or duplicate samples to those used in the LIBS analysis. It has been found that LIBS analytical results generally agree with those obtained with ICP-MS. Zafar et al [ 103 ] spectroscopic analysis of samples from Pakistan was conducted using the LIBS technology coupled with the LA-TOF-MS technology. An Nd: YAG laser (532 nm) was used to generate the plasma, and the optical spectrum was captured using four spectrometers.…”
Section: Quality Assurance Chemical Constituent and Risk Assessment O...mentioning
confidence: 99%